Emerging Technology: What is it - Halaweh,Mohanad (Universidad Alberto Hurtado. Facultad de Economía y Negocios, 2013)
The term emerging technology (ET) has been frequently used by IT professionals and academics. However, little research has shed light on this term and specified its characteristics and what it means. Therefore, this paper aims to define and conceptualize the characteristics of ET. These characteristics are uncertainty, network effect, unseen social and ethical concerns, cost, limitation to particular countries, and a lack of investigation and research. Several examples of ETs are given to validate these characteristics.